Packed-nanofiber solid phase extraction coupled with HPLC for the determination of chloramphenicol in milk. Issue 46 (29th September 2017) - Chu, Lanling; Deng, Jianjun; Kang, Xuejun
Abstract : A sensitive analytical method based on packed-nanofiber solid phase extraction (PFSPE) and high performance liquid chromatography (HPLC) has been developed for determining chloramphenicol (CAP) in milk. Abstract : A sensitive analytical method based on packed-nanofiber solid phase extraction (PFSPE) and high performance liquid chromatography (HPLC) has been developed for determining chloramphenicol (CAP) in milk. Polystyrene–polyvinylpyrrolidone (PS–PVP) composite nanofibers were fabricated by electrospinning and utilized to prepare a home-made extraction device. With optimal conditions, 12 min of HPLC analysis with isocratic elution was successfully applied to determine CAP in milk. The analyte was separated well and blank milk did not disturb determination, the linearity was good in the range of 0.5–10 μg L −1, and the recoveries were in the range of 97.5–104.0%. The intra-day and inter-day RSDs for spiked samples were respectively 4.6–7.1% and 8.4%, all below 10%. The limit of detection (LOD) was determined to be 0.2 μg L −1 . Due to its simplicity, low-cost and time-saving, the method has the potential to be applied to monitor antibiotic residues in dairy products with complex matrices.